561 DuoBody®-PD-L1×4–1BB (GEN1046) induces superior immune-cell activation, cytokine production and cytotoxicity by combining PD-L1 blockade with conditional 4–1BB co-stimulation. (9th November 2020) - Muik, Alexander; Altintas, Isil; Kosoff, Rachelle; Gieseke, Friederike; Schödel, Kristina; Salcedo, Theodora; Burm, Saskia; Toker, Aras; Kranz, Lena; Vormehr, Mathias; Eisel, David; Fereshteh, Mark; et al.
Abstract : Background: Checkpoint inhibitors targeting the PD-1/PD-L1 axis (CPI) have changed the treatment paradigm and prognosis for patients with advanced solid tumors; however, many patients experience limited benefit due to treatment resistance. 4-1BB co-stimulation can activate cytotoxic T-cell- and NK-cell-mediated anti-tumor immunity and has been shown to synergize with CPI in preclinical models. DuoBody-PDL1×4-1BB is a first-in-class, Fc-silenced, bispecific next-generation checkpoint immunotherapy that activates T cells through PD-L1 blockade and simultaneous PD-L1-dependent 4-1BB co-stimulation. Here we present preclinical evidence for the mechanism of action of DuoBody-PD-L1×4-1BB, and proof-of-concept using mouse-reactive mbsAb-PD-L1×4-1BB in vivo. Methods: RNA sequencing analyses was performed on primary human CD8+ T cells that were co-cultured with PD-L1+ monocytes in the presence of anti-CD3/anti-CD28 and test compounds. T-cell proliferation and cytokine production were analyzed in primary human T-cell and mixed lymphocyte reaction (MLR) assays in vitro, and using patient-derived tumor-infiltrating lymphocytes (TILs). Cytotoxic activity was assessed in co-cultures of CLDN6+PD-L1+ MDA-MB-231 tumor cells and CLDN6-TCR+CD8+ T cells. Anti-tumor activity of mbsAb-PD-L1×4-1BB was tested in vivo using the CT26 mouse tumor model. Immunophenotyping of the tumor microenvironment (TME), tumor-draining lymph nodes (tdLNs) and peripheral blood was performed by flow cytometry. Results: DuoBody-PD-L1×4-1BB significantly induced expression of genes associated with immune cell proliferation, migration and cytokine production in activated CD8+ T cells, which were not altered by CPI. DuoBody-PD-L1×4-1BB dose-dependently enhanced expansion of human TILs ex vivo. DuoBody-PD-L1×4-1BB dose-dependently enhanced T-cell proliferation and pro-inflammatory cytokine production in vitro (e.g. IFNγ and TNFα; in polyclonal and antigen-specific T-cell proliferation assays and MLR), which was dependent on crosslinking to PD-L1+ cells and superior to CPI or the combination of Fc-silenced PD-L1- and 4-1BB-specific antibodies. DuoBody-PD-L1x4-1BB induced upregulation of degranulation marker CD107a and granzyme B in CD8+ T cells, resulting in antigen-specific T-cell-mediated cytotoxicity of MDA-MB-231 tumor cells in vitro, superior to CPI. In mice bearing subcutaneous CT26 tumors, a model that was insensitive to PD-L1 blockade, mbsAb-PD-L1×4-1BB elicited tumor rejection in the majority of the mice at active dose levels and significantly improved survival. Dose-dependent anti-tumor activity was associated with expansion of tumor antigen-specific T cells in the blood and enhanced immune-cell activation in tdLNs and TME. Conclusions: Combining PD-L1 blockade with conditional 4-1BB co-stimulation using bispecific antibodies induced T-cell activation, expansion, and cytotoxic activity in vitro and potent anti-tumor activity in vivo superior to CPI. DuoBody-PD-L1×4-1BB is currently being evaluated in patients with advanced solid tumors in a first-in-human trial (NCT03917381 ). Ethics Approval: All mice studies were performed by BioNTech SE at its research facilities in Germany, and the mice were housed in accordance with German federal and state policies on animal research. All experiments were approved by the regulatory authorities for animal welfare in Germany. The use of tumor tissue resections was approved by BioNTech SE's Ethics Board, approval number 837.309.12 (8410-F).